RELATIONSHIPS BETWEEN HYDROPHYSICAL AND GEOELECTRIC PARAMETERS IN VOLCANIC ROCKS (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
A flow rate of ground water streams is necessary to determine for water balance calculations, as well as for setting up the locations of prospecting boreholes. In case of lack of hydrogeological data for solving the definite problems in practice it is proposed to use both hydrodynamic and geophysical data based on correlation relationships. A number of examples of ground water streams discharges discovered at Sevan Lake basin territories has been discussed in the article.
Keywords: hydrophysical and geoelectric parameters; volcanic rocks; ground water streams; Sevan Lake